THE PRESERVATION OF HOMBO BATU TRADITION IN RELATION TO STUDENT ATTITUDES AND INTERESTS AT SMA NEGERI 1 TELUK DALAM - Darmawan Harefa (Universitas Nias Raya, 2026)
This study aims to analyze the preservation of the Hombo Batu tradition in relation to the attitudes and interests of students at SMA Negeri 1 Teluk Dalam, South Nias Regency. The study employed a quantitative approach with a correlational descriptive method. The population consisted of all students at SMA Negeri 1 Teluk Dalam, with a sample of 120 students selected through proportional random sampling. Data were collected using a Likert-scale questionnaire, which was first tested for validity and reliability. The data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results indicate that most students have a positive attitude (mean = 3.85) and a high level of interest (mean = 3.78) toward the Hombo Batu tradition. Both attitude and interest variables showed a significant positive correlation with tradition preservation, with correlation coefficients of r = 0.62 and r = 0.57, respectively (p < 0.05). Multiple linear regression analysis revealed that 56% of the variance in tradition preservation can be explained by students’ attitudes and interests, with attitude contributing more strongly than interest. These findings confirm that positive attitudes and high interest are key psychological factors in promoting students’ active involvement in local cultural preservation. Based on these results, it is recommended that schools and communities implement education programs based on local cultural values and extracurricular activities that foster students’ positive attitudes and interest in the Hombo Batu tradition, thereby ensuring the sustainability of this cultural heritage among younger generations.